A New Species of Derris Lour. from India - Sahni, K. C.; Naithani, H. B. (Indian Forester, 1976)
A new species of Derris Lour.; D. leanjilalli Sahni and Naithani from Uttar Pradesh (India) is described. Allied to D. manticola (Kurz) Prain. Differs in glabrous nature of petiole, rhachis and pedice1s; leaftets-9, ovate-oblong, notched at tip; calyx cup glarous entire or minutely toothed. The species is being named in honour of Late Sri P.C. Kanjilal, I.F.S. for his contributions of Forest Botany of Uttar Pradesh.